A dense ring of the trans-Neptunian object Quaoar outside its Roche limit - Morgado, B. E.; Sicardy, B.; Braga-Ribas, F.; Ortiz, J. L.; Salo, H.; Vachier, F.; Desmars, J.; Pereira, C. L.; Santos-Sanz, P.; Sfair, R. [UNESP]; de Santana, T. [UNESP]; Assafin, M.; et al. (Springer Nature, 2023)
Planetary rings are observed not only around giant planets1, but also around small bodies such as the Centaur Chariklo2 and the dwarf planet Haumea3. Up to now, all known dense rings were located close enough to their parent bodies, being inside the Roche limit, where tidal forces prevent material with reasonable densities from aggregating into a satellite. Here we report observations of an inhomogeneous ring around the trans-Neptunian body (50000) Quaoar. This trans-Neptunian object has an estimated radius4 of 555 km and possesses a roughly 80-km satellite5 (Weywot) that orbits at 24 Quaoar radii6,7. The detected ring orbits at 7.4 radii from the central body, which is well outside Quaoar’s classical Roche limit, thus indicating that this limit does not always determine where ring material can survive. Our local collisional simulations show that elastic collisions, based on laboratory experiments8, can maintain a ring far away from the body. Moreover, Quaoar’s ring orbits close to the 1/3 spin–orbit resonance9 with Quaoar, a property shared by Chariklo’s2,10,11 and Haumea’s3 rings, suggesting that this resonance plays a key role in ring confinement for small bodies.